Coronary Artery and Pulmonary Artery Fistula Originated from Significant Stenosis in the Left Anterior Descending Artery. (12th February 2013) - Kunt, Alper Sami
Abstract : Coronary artery fistula (CAF) is defined as a rare anomalous connection between a coronary artery and a major vessel or a cardiac chamber. We report a case of a left anterior descending coronary (LAD) stenosis and coronary artery fistula between the LAD coronary artery and the pulmonary artery (PA). CAF is often diagnosed by coronary angiogram. We describe our diagnostic approach and review the literature on the epidemiology, the pathophysiology, the diagnostic modalities, and the treatment options.